Inteligibilidade, dualidade. O sentimento de inteligibilidade em Fernando Gil - Sousa, Inês (Trabalhos de Antropologia e Etnologia, 2020)
Belief, intuition, and subjectivity are, according to Fernando Gil’s concept of intelligibility, core dimensions of the knowledge, as well as of his understanding. The intelligibility is thus conceived as a personal reconstruction of the knowledge operations lead by the subject, such a process ending up on an intellectual feeling called intelligibility feeling. The main aim of this paper is to investigate how the formal thought duality thesis (as formulated by Gilles-Gaston Granger) could contribute to clarify the nature of the intelligibility feeling, as well as the philosophical status of the understanding. This paper is composed of two chief moments, whose goals are as follows: 1) to analyse the definition of the duality as a category of the formal thought; 1.1.) to present and to discuss some ontological and epistemological aspects of the formal thought; 1.2.) to suggest the form-content opposition as a model underlying every signification process; 2) to discuss the Fernando Gil’s hypothesis according to which the different aspect of the duality in 2.1.) logic, 2.2) philosophy of knowledge, and 2.3) scientific explanation, points towards three distinct modalities of the intelligibility feeling. The former topic should allows us to conclude that, on the one hand, the formal thought duality thesis legitimates the distinction between understanding and explanation, and, on the other hand, it shows that the explanation supposes the understanding. This last aspect suggests a relationship amongst the first person and third person authority, in other words, it reveals an interplay between the epistemic and the epistemological levels.